The Application of Pearls in Traditional Medicine of China and Their Chemical Constituents, Pharmacology, Toxicology, and Clinical Research - Song, Yinglian; Chen, Wanyue; Fu, Ke; Wang, Zhang (Frontiers in Pharmacology, 2022)
Although pearls are well known by most people, its medicinal value has not been widely spread. This article systematically collates the medicinal history of pearls over two thousand years in China, such as application of pearls in traditional medicine of China and its various preparations, as well as the progress of its chemical constituents, pharmacology, toxicology and clinical research. Pearls from three different sources are used as medical materiel by 9 nationalities and 251 prescription preparations in China. In addition, pearls contain various inorganic constitutes such as calcium carbonate, trace elements and water, as well as organic constitutes such as amino acids. In terms of pharmacology, pearls have many effects such as calming, improving cognitive ability, anti-epileptic, promoting bone growth and regeneration, promoting the proliferation and migration of human microvascular endothelial cells, protecting the heart, anti-hemolysis, anti-oxidation, etc.. In terms of toxicology, pearls are safe to take for a long time without obvious adverse reactions. In terms of clinical, pearls have been used to treat many diseases and conditions, such as convulsions, epilepsy, palpitations, eye diseases, ulcer diseases, and skin diseases or skin lesions. This article can provide a reference for the application and research of pearls in the future.